2015
DOI: 10.4314/ahs.v15i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of delivering HPV vaccine to girls aged 10 to 15 years in Uganda

Abstract: Background: Cervical cancer is a leading cause of mortality among women in Uganda. The availability of the human papillomavirus (HPV) vaccine presents an opportunity to prevent cervical cancer. The Government of Uganda conducted a demonstration project exploring the feasibility of two delivery strategies. Objective: To explore the feasibility of two HPV vaccine delivery strategies: 1) a stand-alone school-based strategy that selected girls based on their enrolment in grade 5 (known as the "grade-based" strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 15 publications
(20 reference statements)
3
40
0
Order By: Relevance
“…A mentionable number of participants had not yet had sexual intercourse (20%) in this cohort. Similar studies about HPV vaccine acceptability have also shown that a number of AYA had not yet engaged in sexual activity and therefore were still ideal candidates to receive the HPV vaccine Mugisha et al, 2015). Findings from this study demonstrate favourable acceptability towards the HPV vaccine among a population who are at the highest risk of developing HPV related cancers and unable to afford the vaccine.…”
Section: Acceptability Of the Hpv Vaccine: Selfsupporting
confidence: 59%
See 1 more Smart Citation
“…A mentionable number of participants had not yet had sexual intercourse (20%) in this cohort. Similar studies about HPV vaccine acceptability have also shown that a number of AYA had not yet engaged in sexual activity and therefore were still ideal candidates to receive the HPV vaccine Mugisha et al, 2015). Findings from this study demonstrate favourable acceptability towards the HPV vaccine among a population who are at the highest risk of developing HPV related cancers and unable to afford the vaccine.…”
Section: Acceptability Of the Hpv Vaccine: Selfsupporting
confidence: 59%
“…A study examining the feasibility of HPV vaccines for girls in Uganda, interviews and focus groups were conducted with key informants including health workers, teachers, and national health officials. The goal of the cross-sectional study was to better understand the most appropriate HPV vaccine (bivalent) delivery strategy for young women aged 10-15 years (Mugisha et al, 2015). Vaccine uptake and acceptability rates were reported and evaluated for two different delivery strategies in two Ugandan districts: grade-based (grade 5) and age-based (10-year-olds).…”
Section: Uptake Of the Hpv Vaccine: Low-and Middle-income Countriesmentioning
confidence: 99%
“…Vaccinations have been identified as the most common type of intervention in schools in at least 35 countries or territories [9], and there is evidence of effectiveness from primary studies regarding feasibility of school-based vaccination programs [48,49]. Yet no SRs on vaccinations fulfilled the inclusion criteria for this overview, suggesting the need for these SRs to be conducted.…”
Section: Overall Effectiveness Of School Health Servicesmentioning
confidence: 99%
“…21,22 To study these questions, PATH partnered with ministries of health in four low-and middle-income countries-India,Peru,Uganda,andVietnam-tocarryoutdemonstrationprograms. 23 Conductedfrom2007-2010andreachingfrom4000 to25000youngadolescentgirls,theseprogramsresultedin56%-99% three-dosevaccinecoverage,illustratedtheacceptabilityandfeasibilityofsuchprograms,estimatedthecostsofHPVvaccinedeliveryin low-resourcesettings, [23][24][25][26][27][28][29][30][31] andprovidedaguidefortheimplementation of such programs in other countries. 32 In addition, Merck & Co establishedtheGardasilAccessProgram(GAP)in2009.…”
Section: Early Pilots and National Introductionsmentioning
confidence: 99%